(untitled) (ACME, 2024)
Pindar’s Olympian 13, dedicated to Xenophon of Corinth, displays two macroscopic features: first, extensive catalogues of the victories achieved by Xenophon’s family; and second, an accumulation of myths closely related with the city of Corinth, namely the myths of Sisyphos, Medea, Glaukos, and Bellerophon. This connection with Corinth has been strongly emphasized, especially with regard to the Oligaithidai family and to the myths of Medea and Sisyphos reported in Eumelos’ lost poem Korinthiaká. Nevertheless, the ode seems to display typical devices for entertaining secondary audiences. I argue that Pindar’s accounts of myths are deliberately generic, in order to allow for possible re-performance at festivals and symposia. On the other hand, the accuracy of the victories catalogue could also have a rhetorical function, in reperformance scenarios, in order to give future listeners the feeling of being in the place of the first performance (a device often referred to as “pseudo-intimacy”).